The effect of merocel nasal packing use on cognitive functions - Arslan, Fatih; Kokulu Arslan, Tuğba (ENT Updates, 2020)
Objective: It is known that the use of nasal packing has many disadvantages. The aim of this study was to investigate the effects of short-term nasal obstruction due to nasal packing on cognitive functions. Methods: The study group consisted of 40 patients who had nasal congestion due to unilateral nasal septal deviation and for whom septoplasty was planned with a merocel pack to be used as a nasal pack at the end of surgery. All surgeries were performed under local anesthesia using 10 cc of jetocaine ampoule. Brief Symptom Inventory Test (BSI), Visual Analog Scale (VAS), Serial Digit Learning Test (SDL), Stroop Test, Visual Aural Digit Span Test (VADS) and P300 test were used to evaluate cognitive functions, symptoms of concentration difficulties and blunted affect both preoperatively and peroperatively before nasal pack removal. Results: All symptoms showed significant per-operative (with a nasal pack in place) deterioration in all patients (p<0.001) on the VAS. The mean per-operative SDL (16.34±5.77), Stroop Test (26.67±3.39), BSI (22.25±11.95) and VADS (21.13±3.44) scores showed significant deterioration compared with mean preoperative Stroop Test (20.06±3.14), SDL (22.38±4.34), VADS (25.86±2.92) and BSI (32.58±12.49) scores (p<0.001). The peroperative and preoperative P300 latency and amplitude values showed a significant difference (p<0.001). Conclusion: The use of a nasal pack, which closes both nasal passages fully, such as a merocel pack, has negative effects on cognitive functions such as the ability to focus and maintain concentration.